2018
DOI: 10.1111/jcmm.13727
|View full text |Cite
|
Sign up to set email alerts
|

Dipalmitoylphosphatidic acid inhibits breast cancer growth by suppressing angiogenesis via inhibition of the CUX1/FGF1/HGF signalling pathway

Abstract: Tumour growth depends on a continual supply of the nutrients and oxygen, which are offered by tumour angiogenesis. Our previous study showed that dipalmitoylphosphatidic acid (DPPA), a bioactive phospholipid, inhibits the growth of triple‐negative breast cancer cells. However, its direct effect on angiogenesis remains unknown. Our work showed that DPPA significantly suppressed vascular growth in the chick embryo chorioallantoic membrane (CAM) and yolk sac membrane (YSM) models. Meanwhile, tumour angiogenesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Upregulation of CUX1 stimulated proliferation, tumor growth, resistance to apoptosis and angiogenesis in Pnet (8). In the present study, CUX1 functioned as a transactivator for MMP9 transcription and induced the proliferation of pNET cells (potentially through modulating the transcription of certain effectors, for example p21, FGF1, VAV2), which was consistent with previous studies (44)(45)(46).…”
Section: Discussionsupporting
confidence: 93%
“…Upregulation of CUX1 stimulated proliferation, tumor growth, resistance to apoptosis and angiogenesis in Pnet (8). In the present study, CUX1 functioned as a transactivator for MMP9 transcription and induced the proliferation of pNET cells (potentially through modulating the transcription of certain effectors, for example p21, FGF1, VAV2), which was consistent with previous studies (44)(45)(46).…”
Section: Discussionsupporting
confidence: 93%
“…The final score was the average of five random selected regions. It graded as follows: -(0), + (1-4), ++ (5-8) and +++ (9)(10)(11)(12). Samples with final scores ++ or +++ were graded positive, andor + as negative.…”
Section: Tissue Specimens and Immunohistochemistrymentioning
confidence: 99%
“…The expression level of FGF1 and FGFR1 in these cancers indicated that FGF1 induce the invasion and metastasis of tumor cells. In cancer cells, amplified FGF1 expression promotes the proliferation and migration ability of tumor cells (7)(8)(9)(10). However, its expression level in CRC tissues and its expression correlated with clinical indicators and survival, have not been fully elucidated (11).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that angiogenesis is dysregulated in various pathological processes, leading to various diseases, including cancer, cardiovascular disease, inflammation, and obesity (Carmeliet and Jain, 2000;Carmeliet, 2003;Srivastava et al, 2018). It has been established that the abnormal formation of blood vessels is effective as a treatment for patients with cancer, chronic liver disease, cardiovascular disease or other diseases; therefore, using anti-angiogenic agents as inhibitors has become a major therapeutic strategy (Liao et al, 2014;Chen et al, 2018;Srivastava et al, 2018). Currently, several angiogenesis inhibitors that specifically target VEGF, VEGFR, or other specific genes that are involved in angiogenesis can prolong life expectancy in patients with advanced colon cancer and are now being investigated in clinical trials alone or in combination with conventional therapeutic approaches of both cancer and retinal disease (Hurwitz et al, 2004;Avery et al, 2006).…”
Section: Discussionmentioning
confidence: 99%